Solidaritas Digital Tanpa Organisasi Formal: Menjelaskan Kemunculan Kembali #SEAblings di Asia Tenggara - Kholifatus Saadah; Arum Tri Utami (Universitas Bosowa, 2026)
The #SEAblings movement is a spontaneous regional solidarity phenomenon that emerged in Southeast Asia in 2025, triggered by the death of online motorcycle taxi driver Affan Kurniawan during protests in Jakarta. Without formal structure or identifiable leadership, the movement re-emerged in early 2026 when the Day6 concert incident in Kuala Lumpur sparked tensions between Southeast Asian and South Korean netizens. This article aims to explain why #SEAblings was able to re-emerge without reconstructing its resources from scratch. Using a qualitative-interpretive approach from Neumann and document analysis of news sources and social media activity from August 2025 to March 2026, this article employs Resource Mobilization Theory as developed by Edwards & McCarthy as its main analytical framework, supported by Earl & Kimport's argument regarding digital infrastructure as a substitute for formal organization. The analysis reveals that #SEAblings operates through two primary resources: social-organizational resources in the form of latent networks and digital platform infrastructure built during the first wave, and cultural resources in the form of tactical repertoires, regional solidarity narratives, and visual artifacts that continued to circulate outside periods of active mobilization. The re-emergence of the movement in 2026 was not a new phenomenon, but rather a reactivation of pre-existing resources triggered by an external event. These findings suggest that RMT needs to broaden its definition of resources to accommodate leaderless digital movements, where platforms and collective identity function as mobilizing infrastructure that substitutes for formal organization.